25 Evidence based training for hostel staff around supporting homeless people with deteriorating health. Issue 3 (1st September 2018) - Hudson, Briony F; Shulman, Caroline; Kennedy, Peter; Brophy, Niamh; Stone, Patrick
Abstract : Introduction: Many people experiencing homelessness remain in homeless hostels as their health deteriorates due to lack of alternative places of care (Shulman et al. 2017). Palliative care services are rarely involved and hostel staff face significant emotional and practical difficulties (Hudson et al. 2017). We developed evidence-based training for hostel staff around supporting residents with deteriorating health. Aims: To pilot and evaluate the impact of training. Methods: Mixed methods pre-and-post training evaluation. Knowledge of palliative care confidence in and openness to supporting residents with deteriorating health and work-related stress were assessed at baseline and immediately post-training using a novel questionnaire. Following training group discussions were facilitated and participants identified team goals for implementation. Additional focus groups were held after three months. Results: All staff from two hostels attended 87% completed the course (n=21). Modest improvements in knowledge confidence openness and work-related stress were observed. Participants particularly valued the inclusion of strategies for identifying and addressing their emotional needs. At three months team goals were partially met. Identification and recognition of palliative care needs had improved. However the recovery focused ethos of hostels and significant staff turnover limited change. Systems designed to monitor 'recovery' did not accommodate or encourage a person-centred approach for people with deteriorating health. Conclusions: Training in isolation is not enough for system change. Recommendations include embedding ongoing training into routine practice identifying champions to promote multidisciplinary working and incorporating flexibility in outcome measures to reflect complexity in person-centred care including where recovery may not be realistic. References: . Hudson BF, Shulman C, Low J, Hewett N, Daley J, Davis S, Brophy N, Howard D, Vivat B, Kennedy P, Stone P. Challenges to discussing palliative care with people who are homeless: A qualitative study. BMJ Open2017;7:e017502. doi:10.1136/bmjopen-2017-017502 . Shulman C, Hudson BF, Low J, Hewett N, Daley J, Kennedy P, et al. Homelessness at the end of life: A qualitative analysis of the barriers in providing palliative care for people who are homeless. Palliative Medicine2017. https://doi.org/10.1177/0269216317717101